2021
DOI: 10.1002/1873-3468.14245
|View full text |Cite
|
Sign up to set email alerts
|

Secreted acid phosphatases maintain replicative lifespan via inositol polyphosphate metabolism in budding yeast

Abstract: Secreted acid phosphatases (APases) dephosphorylate extracellular organic phosphate compounds to supply inorganic phosphate (Pi) to maintain cellular functions. Here, we show that APases are necessary to maintain a normal replicative lifespan in Saccharomyces cerevisiae. Deletion of all four APase genes shortened the lifespan in yeast strains on synthetic media (irrespective of the concentrations of Pi in the media), but it did not affect the intracellular ortho‐ and polyphosphate levels. Deletion of inositol‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Phosphate is an important determinant for lifespan regulation in many organisms. In yeast, it was shown that high levels of intracellular IP 6 reduce the lifespan [53]: research on knockout mutants of different secreted acid phosphatases (APases such as PHO3, PHO5, PHO11, PHO12) demonstrated a shorter lifespan, regardless of the levels of external phosphate compounds; to uncover the substrates through which APases exert their lifespanregulatory effects, the study conducted a screening involving the disruption of enzymes in the polyphosphate pathway. The results revealed a connection between a shorter lifespan and higher IP 6 levels.…”
Section: Lifespan and Telomere Lengthmentioning
confidence: 99%
“…Phosphate is an important determinant for lifespan regulation in many organisms. In yeast, it was shown that high levels of intracellular IP 6 reduce the lifespan [53]: research on knockout mutants of different secreted acid phosphatases (APases such as PHO3, PHO5, PHO11, PHO12) demonstrated a shorter lifespan, regardless of the levels of external phosphate compounds; to uncover the substrates through which APases exert their lifespanregulatory effects, the study conducted a screening involving the disruption of enzymes in the polyphosphate pathway. The results revealed a connection between a shorter lifespan and higher IP 6 levels.…”
Section: Lifespan and Telomere Lengthmentioning
confidence: 99%